Amniotic epithelial cells from the human placenta potently suppress a mouse model of multiple sclerosis. - Yu Han Liu (Public Library of Science (PLoS), 2012)
Human amniotic epithelial cells (hAEC) have stem cell-like features and immunomodulatory properties. Here we show that hAEC significantly suppressed splenocyte proliferation in vitro and potently attenuated a mouse model of multiple sclerosis (MS). Central nervous system (CNS) CD3(+) T cell and F4/80(+) monocyte/macrophage infiltration and demyelination were significantly reduced with hAEC treatment. Besides the known secretion of prostaglandin E2 (PGE2), we report the novel finding that hAEC utilize transforming growth factor-β (TGF-β) for immunosuppression. Neutralization of TGF-β or PGE2 in splenocyte proliferation assays significantly reduced hAEC-induced suppression. Splenocytes from hAEC-treated mice showed a Th2 cytokine shift with significantly elevated IL-5 production. While transferred CFSE-labeled hAEC could be detected in the lung, none were identified in the CNS or in lymphoid organs. This is the first report documenting the therapeutic effect of hAEC in a MS-like model and suggest that hAEC may have potential for use as therapy for MS.